RHEOLOGICAL STUDY ON THE PARAMETERS AFFECTING THE VISCOSITY OF THE GREEN SOLUTION CONSISTING SLS AND LTTM - Shabrina Sri Riswati; Rini Setiati; Suryo Prakoso; Paramita Jaya Ratri; Ardak Yskak; Rayhan Irvan (Universitas Trisakti, 2023)
Enhanced Oil Recovery (EOR) is known to effectively improve oil recovery by producing the residual oil saturation in a reservoir. Many chemicals for injected fluid in EOR are synthetic and harmful to the environment. Aims: This study aims to characterize a newly developed green solution consisting of Sodium Lignosulfonate (SLS) and a Low Transition Temperature Mixture (LTTM) for injection agent. Methodology and Results: The concentration of surfactant was defined using weight percentage, which was calculated from the portion of the total weight of LTTM. The characterization was approached by analyzing the behavior of the green solution based on the power law analysis of the rheological measurement. The analyses of value, viscosity, shear rate, and shear stress were carried out. Increasing in viscosity was caused by the additional molecular mass of sucrose in the solution. This study found that the SLS concentration and LTTM ratio affects the rheological behavior of the green solution. Conclusion, significance, and impact study: According to the results, adding the SLS concentration increases the probability of the green solution becoming an EOR agent by showing shear-thinning behavior. Further studies are required to ensure the feasibility of the green solution during the injection period and the propagation in the reservoir.